Moderated-mediation effects of achievement motivation, self-efficacy and anxiety on writing performance among Iraqi EFL undergraduates - Sabti, Ahmed Abdulateef (2019)
Writing, which is deemed an intricate task for many ESL and EFL writers, has been associated with learner variables, such as lack of competency in the intended language. In addition, affective variables such as lack of confidence, motivation, self-efficacy, and anxiety, have also been identified as negatively influencing EFL writing in various studies. The current study aims to examine the relationship of Iraqi EFL writing performance with affective variables, namely writing achievement motivation, writing self-efficacy and writing anxiety. It also attempts to examine a developed moderated mediation model of achievement motivation, self-efficacy and anxiety effects on writing performance among Iraqi EFL undergraduate students. The study adopted a quantitative approach to address the phenomenon under investigation. The participants of the study included 300 Iraqi EFL undergraduate students. Data of the study were collected via four instruments, namely three questionnaires: Second Language Writing Anxiety Inventory (SLWAI) to measure the students’ anxiety towards EFL writing, Writer Self-Perception Scale (WSPS) to measure the students’ self-perception of writing ability, Achievement Goal Questionnaire (AGQ) to elicit information pertaining to the students’ achievement motivational goals towards writing skill, and finally a descriptive writing task. The findings of the study indicate that a small number of the participants had high level of debilitating writing anxiety while a majority had high level of facilitating writing anxiety, writing achievement motivation and writing self-efficacy. In addition, the latter adopted the mastery-approach goal and performance-approach goal as well as attained a satisfactory writing performance, whereas the former adopted performance-avoidance goal and performed disappointingly on the assigned writing task. The findings also reveal that writing self-efficacy was a powerful predictor of students’ writing performance and a significant mediating variable that facilitated the relationship between writing achievement motivation and writing performance. The findings are in support of the social cognitive theory that self-efficacy is a powerful predictor of students’ writing outcomes and has a mediational role. The study also demonstrates that facilitating writing anxiety moderated the relationship between writing self-efficacy and writing performance positively, whereas debilitating writing anxiety moderated that relationship negatively. In addition, the study shows that there was a positive relationship between debilitating writing anxiety and performance-avoidance goal, and they both were negatively correlated with writing performance. These findings are in line with the theories of the affective filter hypothesis (AFH) and achievement goal theory (AGT), which stress that performance-avoidance goals are positively associated with debilitating anxiety, which could lead to an unsatisfactory outcome. The study recommends that EFL instructors need to consider these affective sub-dimensions of debilitating anxiety and performance-avoidance goals in EFL writing instruction in order to facilitate the teaching and learning process of EFL writing.